PEMBELAJARAN BERDIFERENSIASI PADA PEMBELAJARAN MATEMATIKA DI KURIKULUM MERDEKA - Meria Ultra Gusteti; Neviyarni Neviyarni (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2022)
Mathematics learning should be carried out interactively, inspiring, challenging, motivating, fun, and meaningful, as well as accommodating the development of students' creativity, talents, and potential. Students can develop physically and psychologically according to their stages. This is in accordance with the concept of differentiated learning. Differentiated learning is an attempt to harmonize the learning process to meet the learning needs of each student. However, the implementation of differentiated learning, especially in Mathematics learning, is still limited. For this reason, researchers are interested in conducting a literature review related to this matter, both in terms of content, process, product, and learning environment. Writing this literature review aims to (1) describe the nature of differentiated learning, (2) the principles and characteristics of differentiated learning, and (3) analyze the opportunities for implementing differentiated learning in learning mathematics. This literature review is sourced from books and scientific articles. From the results of this analysis, it was concluded that (1) the differentiation approach can be integrated with several learning models such as Problem Based Learning (PBL), Project Based Learning (PjBL) and other models that are adapted to student learning styles; (2) differentiated learning can improve student learning outcomes; (3) differentiated learning can be used in mathematics learning because it can accommodate student learning needs that are adjusted to students' interests, learning styles, profiles and learning readiness